Aplikasi Motif Panji-Sekartaji pada Pendok Keris Gaya Surakarta - Darmojo, Kuntadi Wasi (Acintya, 2019)
Pendok is one part of kris furniture elements that are always attached to warangka or sarong kris. The main function of pendok is to wrap the gandar in order to protect the kris blade. Pendok keris also has other functions, namely symbolic and social functions. Pendok of Surakarta style kris mostly have a form with a variety of ornamental applications. Along with the dynamics of development, there has been an innovation in the application of Panji-Sekartaji motif which represents the development of wayang beber motif. This is in accordance to the basic concept of ornamental variety, with the function of adding beauty so that the pendok, when it is applied to the warangka, will make the kris interesting and beautiful. This writing uses interactive analysis method where data analysis that is used to analize problems related to the application of Panji-sekartaji motif on the pendok of Surakarta-style kris. Keywords: pendok, kris, ornament, motives and Surakarta.